Step-by-step explanation:
![\tt{ 1. \: \: 4 \frac{1}{9} + 1 \frac{1}{2}}](https://tex.z-dn.net/?f=%20%5Ctt%7B%201.%20%5C%3A%20%20%5C%3A%204%20%5Cfrac%7B1%7D%7B9%7D%20%2B%201%20%5Cfrac%7B1%7D%7B2%7D%7D)
⇢ ![\tt{ \frac{37}{9} + \frac{3}{2} }](https://tex.z-dn.net/?f=%20%5Ctt%7B%20%20%5Cfrac%7B37%7D%7B9%7D%20%20%2B%20%20%5Cfrac%7B3%7D%7B2%7D%20%7D)
⇢ ![\tt{ \frac{37 \times 2 + 3 \times 9}{18} }](https://tex.z-dn.net/?f=%20%5Ctt%7B%20%5Cfrac%7B37%20%20%5Ctimes%202%20%2B%203%20%5Ctimes%209%7D%7B18%7D%20%7D)
⇢ ![\tt{ \frac{74 + 27}{18} }](https://tex.z-dn.net/?f=%20%5Ctt%7B%20%5Cfrac%7B74%20%2B%2027%7D%7B18%7D%20%7D)
⇢ ![\tt{ \frac{101}{18}}](https://tex.z-dn.net/?f=%20%5Ctt%7B%20%5Cfrac%7B101%7D%7B18%7D%7D%20)
⇢ ![\boxed{ \tt{5 \frac{11}{18}} }](https://tex.z-dn.net/?f=%20%5Cboxed%7B%20%5Ctt%7B5%20%5Cfrac%7B11%7D%7B18%7D%7D%20%7D)
---------------------------------------------------------
![\tt{ \: 2. \: \: 4 \frac{1}{2} \div \frac{3}{5}}](https://tex.z-dn.net/?f=%20%5Ctt%7B%20%5C%3A%202.%20%5C%3A%20%20%5C%3A%204%20%5Cfrac%7B1%7D%7B2%7D%20%5Cdiv%20%5Cfrac%7B3%7D%7B5%7D%7D)
⇢ ![\tt{ \frac{9}{2} \times \frac{5}{3}}](https://tex.z-dn.net/?f=%20%5Ctt%7B%20%5Cfrac%7B9%7D%7B2%7D%20%20%5Ctimes%20%20%5Cfrac%7B5%7D%7B3%7D%7D%20)
⇢ ![\tt{ \frac{9 \times 5}{2 \times 3}}](https://tex.z-dn.net/?f=%20%5Ctt%7B%20%5Cfrac%7B9%20%20%5Ctimes%205%7D%7B2%20%5Ctimes%203%7D%7D%20)
⇢ ![\tt{ \frac{45}{6}}](https://tex.z-dn.net/?f=%20%5Ctt%7B%20%5Cfrac%7B45%7D%7B6%7D%7D%20)
⇢ ![\boxed{ \tt{7 \frac{3}{6}} }](https://tex.z-dn.net/?f=%20%5Cboxed%7B%20%5Ctt%7B7%20%5Cfrac%7B3%7D%7B6%7D%7D%20%7D)
Hope I helped ! ♡
Have a wonderful day / night ! ツ
▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁
Answer:
D. X-7
Step-by-step explanation:
The table tells you that when x=7, g(x) = 0. In order for g(7) to be zero, at least one factor must be zero when x=7. The only factor on the list that is zero when x=7 is (x-7).
Look at the picture.
We have the equation (1) 12x + 4y = 40.
We know, the sum of the acute angles in a right triangle is 90°.
Therefore we have the equation (2) (12x + 4y) + (17x - y) = 90
Substitute (1) to (2):
40 + 17x - y = 90 <em>subtract 40 from both sides</em>
17x - y = 50 (3)
We have the system of equations:
![\left\{\begin{array}{ccc}12x + 4y = 40&|:4\\17x-y=50\end{array}\right\\\underline{+\left\{\begin{array}{ccc}3x + y = 10\\17x-y=50\end{array}\right}\ \text{add both side of equations}\\.\qquad20x=60\qquad|:20\\.\qquad x=3](https://tex.z-dn.net/?f=%5Cleft%5C%7B%5Cbegin%7Barray%7D%7Bccc%7D12x%20%2B%204y%20%3D%2040%26%7C%3A4%5C%5C17x-y%3D50%5Cend%7Barray%7D%5Cright%5C%5C%5Cunderline%7B%2B%5Cleft%5C%7B%5Cbegin%7Barray%7D%7Bccc%7D3x%20%2B%20y%20%3D%2010%5C%5C17x-y%3D50%5Cend%7Barray%7D%5Cright%7D%5C%20%5Ctext%7Badd%20both%20side%20of%20equations%7D%5C%5C.%5Cqquad20x%3D60%5Cqquad%7C%3A20%5C%5C.%5Cqquad%20x%3D3)
Substitute the value of x to (3)
![17(3)-y=50\\51-y=50\qquad|-51\\-y=-1\to y=1](https://tex.z-dn.net/?f=17%283%29-y%3D50%5C%5C51-y%3D50%5Cqquad%7C-51%5C%5C-y%3D-1%5Cto%20y%3D1)
Answer: x = 3 and y = 1.
Answer:
61 km/s
Step-by-step explanation:
First, you count the number of hours he travelled: 22
Next, divide the distance he travelled, 1342, by the time he travelled, 22, ![\frac{1342}{22} = 61](https://tex.z-dn.net/?f=%5Cfrac%7B1342%7D%7B22%7D%20%3D%2061)